Extracellular vesicles in seminal plasma of Sahiwal cattle bulls carry a differential abundance of sperm fertility-associated proteins for augmenting the functional quality of low-fertile bull spermatozoa - Ankit Pal; Seema Karanwal; Mir Ahmad Habib; Fanny Josan; Vikrant Gaur; Aditya Patel; Muskaan Garg; Mukesh Bhakat; Tirtha K. Datta; Rakesh Kumar (Scientific Reports)
Abstract Poor male fertility significantly affects dairy production, primarily due to low conception rates (CR) in bulls, even when cows are inseminated with morphologically normal sperm. Seminal plasma is a key factor in evaluating the fertilizing ability of bull semen. The extracellular vesicles (EVs) in seminal plasma contain fertility-associated proteins like SPAM1, ADAM7, and SP10, which influence sperm function and fertilizing potential. This study aimed to assess EV-associated fertility proteins in bulls with varying fertility levels and to investigate the effects of seminal plasma EVs (SPEVs) from high-fertility (HF) bulls on the spermatozoa of low-fertility (LF) Sahiwal bulls. Seminal plasma was isolated from the fresh semen of Sahiwal bulls, with four bulls classified as high fertility and three as low fertility. Fertility-associated proteins such as SP10, ADAM7, and SPAM 1 were highly expressed in SPEVs of high-fertility (HF) bulls. PKH26 dye-labeled SPEVs demonstrated significant uptake by spermatozoa at pH 6.8 with ≥ 4 h of co-incubation. Exposure of HF SPEVs to low-fertility (LF) spermatozoa reduced acrosome response, capacitation, and reactive oxygen species (ROS) formation. Our findings suggest that protein repertoires in SPEVs influence sperm activities such as motility, acrosome response, and ROS production. Supplementing LF spermatozoa with HF SPEVs could enhance their functional characteristics, highlighting these proteins as potential resources to modulate cattle bull sperm fertilizing ability.